PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PER (PERMODALAN EKONOMI RAKYAT) PEKANBARU - Manalu, Keke Buang; ', Kasmiruddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the extent to which job stress and work environment affect employee productivity at PT Permodalan Ekonomi Rakyat (PER) Pekanbaru. The research employs a descriptive quantitative method using a survey approach. Data were collected through questionnaires distributed to 80 respondents and analyzed using SPSS version 23. The results indicate that job stress has a significant yet weak influence on productivity (β = 0.032; p < 0.05). In contrast, the work environment has a highly significant and dominant effect (β = 0.844). Simultaneously, both independent variables contribute 77.9% to work productivity. The study concludes that managing job stress and improving the work environment are crucial factors in enhancing employee productivity. Keywords: Job Stress, Work Environment, Productivity, PT PER.